Convegno internazionale “Fiume, paesaggio, difesa del suolo. Superare le emergenze, cogliere le opportunità”, Firenze 10-11 maggio 2006. Presentazione, approccio, obiettivi e temi-chiave - Ercolini, Michele (Ri-Vista. Research for landscape architecture, 2015)
The objective of the international conference is trying to consider landscape river planning a cultural, social and economic investment instead of a “loss”, project that should aim to the control of a landscape that changes but, at the same time, keeps, from an ecological and environmental point of view, harmonic forms and sustainable structures and regenerates itself on the basis of human being needs without damage nature. The necessity of floods defence becomes an opportunity for planning new landscapes, new spaces and new natural and ecologic sceneries.